Multivariate miRNA signatures as biomarkers for non-ischaemic systolic heart failure - Heilmeier, Britta; Keller, Andreas; Frese, Karen S.; Leidinger, Petra; Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Kloos, Wanda; Backe, Christina; Thanaraj, Ann; Brefort, Thomas; Beier, Markus; Hardt, Stefan; et al. (European heart journal, 2013)
Non-ischaemic heart failure is one of the today's most prevalent cardiovascular disorders. Since modern pharmacotherapy has proved to be very effective in delaying disease progression and preventing death, imaging modalities and molecular biomarkers play an important role in early identification and clinical management as well as risk assessment of patients. The present study evaluated for the first time whole peripheral blood miRNAs as novel biomarker candidates for non-ischaemic heart failure with reduced ejection fraction (HF-REF).We assessed genome-wide miRNA expression profiles in 53 HF-REF patients and 39 controls. We could identify and validate several miRNAs that show altered expression levels in non-ischaemic HF-REF, discriminating cases from controls both as single markers or when combined in a multivariate signature. In addition, we demonstrate that the miRNAs of this signature significantly correlate with disease severity as indicated by left ventricular ejection fraction.Our data further denote that miRNAs are potential biomarkers for systolic heart failure. Since their detection levels in whole blood are also related to the degree of left ventricular dysfunction, they may serve as objective molecular tools to assess disease severity and prognosis.
Gesehen am 03.03.2022